Children's views on postsurgical pain in recovery units in Norway: A qualitative study. Issue 11 (13th February 2019) - Smeland, Anja Hetland; Rustøen, Tone; Næss, Torgun; Nybro, Lill; Lundeberg, Stefan; Reinertsen, Hanne; Diseth, Trond H.; Twycross, Alison
Abstract: Aims and objectives: To explore children's postsurgical experiences with pain and pain management in the recovery unit. Background: Children's pain is underestimated and undertreated. Untreated pain can cause unnecessary suffering, increased complication risks and may lead to chronic pain. Research exploring children's experiences with postoperative pain and pain management is limited. Design: A qualitative, exploratory study. The study complied with the Consolidated Criteria for Reporting Qualitative Research (COREQ). Methods: Children ( N = 20), 8–16 years old, took part in semi‐structured interviews about their experiences with pain and postoperative pain management while they were in a recovery unit. Data were collected at two university hospitals in Norway. Content analysis was used to analyse the data. Results: Three themes emerged from the interviews: "children's experiences of what felt unpleasant and painful, " "children's experiences with pain management" and "children's recommendations for future pain management". About half of the children reported moderate to severe pain while in the recovery unit and they did not always tell their nurses when they had pain. They also reported experiencing pain in places other than their surgical wounds and stated that nausea and vomiting felt unpleasant and painful. The children indicated that pain medications and the use of nonpharmacological methods helped them cope with their pain and provided several recommendations about how to improve pain management. Conclusion: Paediatric postoperative pain management remains suboptimal. The children in our study provided useful information about their pain experiences, how to improve pain management and explained why they did not tell their nurses when they were in pain. Relevance to clinical practice: These findings should direct further improvements in paediatric postoperative pain management, such as increased use of pain assessment tools and preparatory information, as well as more appropriate administration of pain medications.